Poverty, psycho-emotional wellbeing, and childrearing: Lived experiences of rural poor Filipino mothers - Jayme, Maria Carla A. (Animo Repository, 2021)
This study examines the meanings rural poor mothers ascribe to their lived experiences of poverty and their perceptions about the relationship among rural poverty, childrearing, and psycho-emotional wellbeing. The participants were selected through purposive sampling based on the study’s set of criteria. The one-on-one phone interviews were semi-structured using open-ended questions. In formulating the categories of the data, the researcher needed to utilize grounded theory procedures. The analysis used narrative inquiry as a method for retrospective meaning-making and as a conceptual starting point in sensitizing the data. The findings show that poverty means enduring deprivation (material and socioeconomic) and being vulnerable to domestic abuse. Childrearing among the mothers involved parental responses towards their children, taking the primary responsibility of childcare, and financial coping strategies. Finally, psycho-emotional wellbeing of the participants is described through negative mental states (suicide ideation, mental stress, sadness, anger) and positive mental states (reliance on God and wellness). The localized meaning and lived experiences of rural poverty, providing in-depth knowledge and context-specific details, among the mothers in the study contribute to the dearth of studies on women and poverty. This study gives voice to and acknowledges the lived experiences of the rural poor mothers.